Molecular evolutionary analysis of the Alfin-like protein family in Arabidopsis lyrata, Arabidopsis thaliana, and Thellungiella halophila. - Yu Song (Public Library of Science (PLoS), 2013)
In previous studies, the Alfin1 gene, a transcription factor, enhanced salt tolerance in alfalfa, primarily through altering gene expression levels in the root. Here, we examined the molecular evolution of the Alfin-like (AL) proteins in two Arabidopsis species (A. lyrata and A. thaliana) and a salt-tolerant close relative Thellungiella halophila. These AL-like proteins could be divided into four groups and the two known DUF3594 and PHD-finger domains had co-evolved within each group of genes, irrespective of species, due to gene duplication events in the common ancestor of all three species while gene loss was observed only in T. halophila. To detect whether natural selection acted in the evolution of AL genes, we calculated synonymous substitution ratios (dn/ds) and codon usage statistics, finding positive selection operated on four branches and significant differences in biased codon usage in the AL family between T. halophila and A. lyrata or A. thaliana. Distinctively, only the AL7 branch was under positive selection on the PHD-finger domain and the three members on the branch showed the smallest difference when codon bias was evaluated among the seven clusters. Functional analysis based on transgenic overexpression lines and T-DNA insertion mutants indicated that salt-stress-induced AtAL7 could play a negative role in salt tolerance of A. thaliana, suggesting that adaptive evolution occurred in the members of AL gene family.